Analysis of Health Disparities Among Different Socioeconomic Groups in Indonesia: Implications for Health Policy - Daniel Ginting; Suharto; Nina Fentiana (Gema Lingkungan Kesehatan, 2024)
The unequal distribution of economic resources can result in disparities in access to health services, particularly in lower-income communities where the lack of resources may limit the ability to obtain services that meet their specific needs. As is often the case in communities with lower economic status, individuals tend to prefer traditional medicine, facilitated by village shamans, over seeking care at nearby health facilities. In some literature, the factors contributing to the difficulty of accessing healthcare in communities with low economic status are attributed to two primary factors: internal factors and external factors. This lack of agency on the part of the community then gives rise to a middle ground in the form of a national health insurance program, commonly referred to as BPJS, which is accessible to people from a range of economic backgrounds. This study employs the descriptive qualitative research method, which involves a systematic and comprehensive examination of a given phenomenon or subject matter, with the objective of providing a detailed account of that phenomenon or subject matter in a way that is both accurate and insightful. The findings indicate that economic status continues to exert a significant influence on the manner in which health services are provided to the Indonesian population.